2016
DOI: 10.1111/mec.13760
|View full text |Cite
|
Sign up to set email alerts
|

A tree of tree frogs around the Black Sea

Abstract: Speciation, the process by which one species evolves into two or more, is a major focus of ongoing debate, particularly regarding the geographic context in which it occurs. Geographic models of speciation tend to fall into discrete categories, typically referred to as allopatric, parapatric and sympatric speciation, according to whether two groups evolve reproductive isolation while geographically isolated, differentiated but connected by gene flow, or completely co‐occurring. Yet molecular studies indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The connection between sex chromosome rearrangements and speciation is being intensively investigated. It was shown that non‐recombining regions of any chromosome might present hotspots for incompatibility that may be a key to speciation . In this article, Irwin argues that in ZW and XY sex‐determination systems, the Z and X chromosomes can play a dominant role in speciation.…”
mentioning
confidence: 97%
“…The connection between sex chromosome rearrangements and speciation is being intensively investigated. It was shown that non‐recombining regions of any chromosome might present hotspots for incompatibility that may be a key to speciation . In this article, Irwin argues that in ZW and XY sex‐determination systems, the Z and X chromosomes can play a dominant role in speciation.…”
mentioning
confidence: 97%
“…5). Intriguingly, both groups W2 of the two species belonged to the western lineage based on the nuclear DNA but had mitochondrial DNA from the eastern clades D4 and C2, suggesting a history of sex-asymmetric hybridization and selection for a particular mitochondrial type in the mixed population (Irwin, 2016). The asymmetric gene flow observed between group W2 and E2 were in support of gene exchange between the terminals of the western and eastern lineages, and the reduced level gene flow at the terminal of the rings support the existence of partial reproductive isolation (Table S5).…”
Section: Ring Distribution and Diversification Rather Than Ring Speciesmentioning
confidence: 99%